Mutations in circulating cell‐free tumour DNA: Predictors of survival in hepatocellular carcinoma. Issue 2 (5th August 2021) - Howell, Jessica; Atkinson, Stephen R.; Pinato, David J.; Khan, Shahid A; Minisini, Rosalba; Burlone, Michela E.; Leutner, Monica; Pirisi, Mario; Büttner, Reinhard; Odenthal, Margarete; Sharma, Rohini
Abstract: Background: Hepatocellular carcinoma (HCC) incidence is increasing worldwide and prognostic biomarkers are urgently needed to guide treatment and reduce mortality. Circulating cell‐free DNA of tumour origin (ctDNA) is a novel, minimally invasive means of determining genetic alterations in cancer. We determined the utility of ctDNA as a prognostic biomarker of survival in HCC. Methods: Plasma cell‐free DNA and matched germline DNA were isolated from patients with HCC (n = 51) and cirrhosis (n = 10). Targeted, multiplex PCR ultra‐deep sequencing was performed using a liver cancer‐specific primer panel for genes ALB, AMPH, APC, ARID1A, ARID2, ATM, AXIN1, BAZ2B, BRAF, CSMD3, CTNNB1, DSE, ERBB2, HNF1A, IGFR2, IGSF10, KEAP1, MET, TP53, UBR3, USP25, ZIC3 and ZNF226 . Associations between mutations in ctDNA and overall survival were analysed using Cox proportional hazards modelling. Results: 114 putative mutations (70 unique) in were detected in plasma ctDNA in 35 of 51 patients with HCC (69%). On univariable analysis, CSMD3 gene mutations were associated with shorter overall survival (Logrank HR 3.18, 95% CI 1.14‐8.86, P  = .027). The median survival time was 15.5 months (IQR 7.77‐16.5 months) in patients with CSMD3 mutations compared with the median survival of 26.5 months (IQR 16.93‐46.07 months) in patients without CSMD3 mutations. Other factors associated with overall survival were advanced BCLC stage (HR 16.52, 95% CI 2.22‐122.94, P  = .006) and Child‐Pugh Class (CPC HR 7.98, 95% CI 2.31‐27.61, P  = .001). Cox proportional hazards modelling showed mutations in CSMD3 remained a significant independent risk for shorter overall survival in HCC when adjusted for age, BCLC stage and Child‐Pugh class (HR 4.91, 95% CI 1.60‐15.02, P  = .005). Conclusion: Detection of CSMD3 mutations in plasma ctDNA is associated with reduced overall survival in HCC patients, adjusted for potential confounding factors.